Openness and education - Meiszner, Andreas; Husmann, Elmar; Squires, Lin (Advances in digital education and lifelong learning, 2013)
This volume takes a look at the emergence of open education as a concept, a production process and a delivery preference in the world of education and learning. Drawing on early lessons from around the globe the book lays out how formal education, workplace learning and lifelong learning have been impacted so far by open education and how they stand to be further impacted by a landscape that is still changing. The book examines the social and economic consequences of open education and provide an insight into the way open education could contribute to a higher level of digital inclusion and to the establishment of new and innovative services of high social and economic merit. Featuring case studies of initiatives, practices and projects this volume illustrates theoretical concepts and emerging models of open education in the context of the latest academic studies and entrepreneurial innovation.